2022
DOI: 10.1007/s10143-022-01805-4
|View full text |Cite
|
Sign up to set email alerts
|

Decompression only versus fusion in octogenarians with spinal epidural abscesses: early complications, clinical and radiological outcome with 2-year follow-up

Abstract: Despite increased life expectancy due to health care quality improvements globally, pyogenic vertebral osteomyelitis (PVO) treatment with a spinal epidural abscess (SEA) remains challenging in patients older than 80 years. We aimed to assess octogenarians for PVO prevalence with SEA and compare after-surgery clinical outcomes of decompression and decompression and instrumentation. A retrospective review of electronic medical records at a single institution was conducted between September 2005 and December 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previous studies from our study group focused on octogenarians have shown that heightened comorbidity rates significantly increase the likelihood of complications and, in certain instances, mortality ( Lenga et al, 2022a , 2022b , 2022c , 2022d , 2023b ). This observation is consistent with a retrospective study of 47 octogenarians with diverse spinal pathologies, where comorbidity rates emerged as a critical factor for adverse events (AEs), exhibiting a prevalence of 17.0%.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies from our study group focused on octogenarians have shown that heightened comorbidity rates significantly increase the likelihood of complications and, in certain instances, mortality ( Lenga et al, 2022a , 2022b , 2022c , 2022d , 2023b ). This observation is consistent with a retrospective study of 47 octogenarians with diverse spinal pathologies, where comorbidity rates emerged as a critical factor for adverse events (AEs), exhibiting a prevalence of 17.0%.…”
Section: Discussionmentioning
confidence: 88%
“…Most often, follow-up was reported as a mean and a range, with further details omitted. It was also typically not clearly reported how many patients may have been excluded from the study due to inadequate follow-up [2,4,5,[9][10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The mean follow-up for Khanna et al was 20.9 months (with a range of 4-45 months) [28]. Lenga et al reported a mean follow-up of 26.6 ± 12.4 months [12].…”
Section: Discussionmentioning
confidence: 99%
“…As already shown in our previous studies on SEA [ 3 , 9 ], patient demographics, comorbidities, American Society of Anesthesiologists (ASA) scores, surgery duration, blood loss, number of treated spinal levels, perioperative and postoperative complications, hospital length of stay (LOS), intensive care unit (ICU) stay, readmission rate, reoperation rate, and mortality rate were retrieved from the patients’ electronic medical records. The age-adjusted Charlson comorbidity index (CCI) was used to assess the comorbidities [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Prompt surgical decompression and evacuation with concurrent antibiotic treatment seem to be state-of-the-art therapy for such a condition, especially in the presence of neurological deficits [ 5 , 8 ]. Previous studies suggested that such therapeutic approaches might benefit older patients or even octogenarians by preserving or improving their neurological condition; nevertheless, a multidisciplinary approach and understanding of their unique needs are important aspects given their poor baseline reserve [ 3 , 9 ]. However, there is a lack of comparative studies involving young and older patients with SEA focusing on the outcomes after surgical management.…”
Section: Introductionmentioning
confidence: 99%